Vulneración de derechos en los hijos habidos bajo matrimonio por parte de sus progenitores en aplicabilidad al régimen de visitas - Fernández Gatñay, Ronal Andrés (2018)
This research work addresses the issue of the violation of rights in children under marriage by their parents in applicability to the visitation regime. A problem that arises when marital relationships enter into crisis and lead to ruptures with separation or divorce, which mainly affects girls and boys who are left in a situation of helplessness or vulnerability in the face of divergences between ex-spouses. parental authority or by possession. The question is that in this type of matrimonial conflicts, what Ecuadorian and international legislation provides in the Constitution - 2008, in the Organic Code of Childhood and Adolescence, where it emphasizes the best interests of the child, and the Civil Code is made invisible which shows the processes that the judge must follow to sentence in favor of the children under marriage, which include the actions that must be carried out to protect their integrity and promote their development. Another important element that is analyzed is that related to the economic and emotional effects that are more disturbing due to the separation of the parents, especially when the break is violent and the right of the father who is left without patria potestas to exercise a regime of visits according to the needs of sharing in an affective way with their children. The general objective that arises in the investigation is "To determine the vulnerability of the rights of the children under marriage caused by ruptures of the matrimonial relations, through the revision of the Cause No 07205-2017-00477 of the Provincial Court of Justice, in perspective analyze the origin, compliance and legal applicability of the visitation regime "added to the specific objectives: a). Analyze the different legal and doctrinal foundations in which the Visiting Regime is framed. b) Extract criteria of professionals on the Visiting Scheme and its consequences in minors. c) Determine the origin of affectation to the rights of minors in application to the Visiting Scheme by their parents. d). Establish possible guidelines that help improve the judicial processes of the Visiting System. Methodologically the research is based on the rational, experiential experiential approach that is akin to the modality of titling the case study. The methods used in introspection are deductive and inductive, descriptive, analytical and exegetical. The technique is the interview and the bibliographic review. The modality is mixed, since the bibliographic information is combined with the information resulting from the interviews and the analysis of the case ventilated in the court. The type is historical, descriptive, bibliographical - documentary. Concepts such as the violation of rights, parental authority, shared tenancy and visitation regime are of great importance, because in the areas of the rights of parents and children, they are consubstantial to the consequences generated by marital breakdowns.